Review of The Role Company Supervision Mechanism in Risk Management Implementation - Cahyani, Mirna; Soewarno, Noorlailie (Esensi: Jurnal Bisnis dan Manajemen, 2021)
This study reviews the supervisory mechanism carried out by the company in the implementation of risk management. This research is qualitative research with literature study method. As a result, internal auditors, audit committees and management accountants work together in supervising the implementation of risk-based audits. Internal auditors have a weak contribution because they prefer a supervisory approach so they are supported by the audit committee. The audit committee supervises the internal auditors and provides suggestions for the next audit process so that it can cover high-risk areas. Meanwhile, the external auditor supervises by ensuring whether the financial statements are presented fairly. This research contributes to expanding the study of the role of supervisory mechanisms in companies for the implementation of corporate risk management.